Welcome to Westonci.ca, your go-to destination for finding answers to all your questions. Join our expert community today! Join our platform to get reliable answers to your questions from a knowledgeable community of experts. Connect with a community of professionals ready to help you find accurate solutions to your questions quickly and efficiently.
Sagot :
Sure, let’s solve the equation step-by-step.
We start with the given equation:
[tex]\[ y + 6 = -3y + 26 \][/tex]
1. Combine like terms on one side:
First, we want to get all terms involving [tex]\( y \)[/tex] on one side of the equation and constant terms on the other side. To do this, add [tex]\( 3y \)[/tex] to both sides of the equation:
[tex]\[ y + 6 + 3y = -3y + 3y + 26 \][/tex]
[tex]\[ 4y + 6 = 26 \][/tex]
2. Isolate the term with [tex]\( y \)[/tex]:
To solve for [tex]\( y \)[/tex], we need to isolate the variable term. Subtract 6 from both sides of the equation:
[tex]\[ 4y + 6 - 6 = 26 - 6 \][/tex]
[tex]\[ 4y = 20 \][/tex]
3. Solve for [tex]\( y \)[/tex]:
Divide both sides of the equation by 4 to solve for [tex]\( y \)[/tex]:
[tex]\[ \frac{4y}{4} = \frac{20}{4} \][/tex]
[tex]\[ y = 5 \][/tex]
So the solution to the equation [tex]\( y + 6 = -3y + 26 \)[/tex] is:
[tex]\[ y = 5 \][/tex]
Hence, the correct answer is:
[tex]\[ y = 5 \][/tex]
We start with the given equation:
[tex]\[ y + 6 = -3y + 26 \][/tex]
1. Combine like terms on one side:
First, we want to get all terms involving [tex]\( y \)[/tex] on one side of the equation and constant terms on the other side. To do this, add [tex]\( 3y \)[/tex] to both sides of the equation:
[tex]\[ y + 6 + 3y = -3y + 3y + 26 \][/tex]
[tex]\[ 4y + 6 = 26 \][/tex]
2. Isolate the term with [tex]\( y \)[/tex]:
To solve for [tex]\( y \)[/tex], we need to isolate the variable term. Subtract 6 from both sides of the equation:
[tex]\[ 4y + 6 - 6 = 26 - 6 \][/tex]
[tex]\[ 4y = 20 \][/tex]
3. Solve for [tex]\( y \)[/tex]:
Divide both sides of the equation by 4 to solve for [tex]\( y \)[/tex]:
[tex]\[ \frac{4y}{4} = \frac{20}{4} \][/tex]
[tex]\[ y = 5 \][/tex]
So the solution to the equation [tex]\( y + 6 = -3y + 26 \)[/tex] is:
[tex]\[ y = 5 \][/tex]
Hence, the correct answer is:
[tex]\[ y = 5 \][/tex]
We appreciate your visit. Our platform is always here to offer accurate and reliable answers. Return anytime. We hope you found what you were looking for. Feel free to revisit us for more answers and updated information. We're dedicated to helping you find the answers you need at Westonci.ca. Don't hesitate to return for more.